PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA SEJAHTERA MART RANTEPAO KABUPATEN TORAJA UTARA - Panimba, Winta; Lusdani, Westerini; Tonapa, Ulfiani (JURNAL ILMIAH EDUNOMIKA, 2024)
The Influence of Price and Service Quality on Purchase Decisions at Sejahtera Mart Rantepao, North Toraja Regency. The problems in this study are: Does the price affect purchasing decisions at Sejahtera Mart Rantepao. Does the quality of service affect purchasing decisions at Sejahtera Mart Rantepao.) Do prices and service quality affect purchasing decisions at Sejahtera Mart Rantepao. The population in this study are consumers who make purchases at Sejahtera Mart Rantepao. Sampling in this study is Nonprobability Sampling. The data analysis technique used is instrumenttest, classical assumption test, hypothesis testing. The results of the study The price has a significant effect on purchasing decisions because the value of t_count>t_table is 0.254>0.2006 and the resulting significance is 0.800 t_table or 0.677>0.2006 and the resulting significant is 0.500